Tennesseans at War, 1812-1815 : Andrew Jackson, the Creek War, and the Battle of New Orleans - Kanon, Tom, 1951- (Book collections on Project MUSE., 2014)
Tennesseans at War, 1812-1815 by Tom Kanon tells the often forgotten story of the central role citizens and soldiers from Tennessee played in the Creek War in Alabama and War of 1812. Although frequently discussed as separate military conflicts, the War of 1812 against Great Britain and the Creek War against Native Americans in the territory that would become Alabama were part of the same forceful projection of growing American power. Success in both wars won for America security against attack from abroad and vast tracks of new land in "the Old Southwest." In Tennesseans